Analisis Terjadinya Gol di Piala Menpora 2021 - Amiersha Syah Shavira; Mokhamad Nur Bawono (Indonesian Journal of Kinanthropology (IJOK), 2022)
Background: This study aims to determine the occurrence of the goal process in the 2021 Menpora Cup competition. Methods: This research is a qualitative descriptive by using the instrument of video analysis results in the occurrence of goals in the Menpora Cup 2021. Video analysis technique, the videos obtained are analyzed using percentages to determine the occurrence of the goal process in the Menpora Cup 2021 competition. Results: Participants who took part in this competition through 3 types of items, the results obtained that the skills in the process of scoring soccer goals for participants participating in the 2021 Menpora Cup competition were classified as moderate, from 23% through penalty goals, 55.1% through open play goals and the remaining 21, 9% through setpiece goals. Conclusions: Open play There was 55.1% occurring in the group preliminary matches up to the final round, Set piece This type of goal process occurred 21.9% in matches, Penalty occurred by 23% in the Menpora Cup tournament in 2021. that the process of goal occurrence In the 2021 Menpora Cup, a lot of things happened through open play. Based on the results of this study, the researchers suggest that the provision of physical exercise and basic techniques of playing soccer should be given from an early age so that it is easier for players to understand and master. Keywords: goal; menpora cup; soccer